Costeo dos fases y el time driven activity based cost en una planta de manufactura - Salas-Hidalgo, Luis Miguel (2022)
Calculating the production costs of a product in a manufacturing company within hundreds of products is not an easy task to understand and perform, since we have a variety of resources that are not direct to the product, which first have to be distributed to activity groups and then from activity groups to outputs. The Time Driven Activity Based Cost (TDABC) proposes the use of time at all levels, but we have found that in manufacturing processes this is not entirely feasible, since many of the resources not directly related to the product have to be distributed based on another first-level inducer, proceeding with the distribution of the other non-direct resources to the groups of activities based on time, as indicated by the TDABC procedure. The proposal that we propose will achieve a combination of the TDABC with the allocation of indirect manufacturing costs to the product through a process called two-stage costing. With this we will demonstrate that both procedures can be combined and establish a process that allows a correct allocation of resources based on the calculation of non-direct costs to a product or service in a manufacturing plant efficiently.